Multi-criterian methods for selection of rational strategies of diversification of building enterprises in uncertainty - Yuanyuan Li (КНУБА, 2019)
A thorough review and comparative analysis of well-known multi-criteria decision-making methods used for the task of ranking or selecting rational alternatives has been conducted in this article. It is revealed that most methods take into account the conditions of ambiguity of the environment. Since the problem of implementing diversification strategies is usually financially costly, it is proposed to use for selecting strategies for diversifying the activities of construction enterprises, a set of methods that focus on multicriteria decision-making under uncertainty. It is desirable to take into account the possible blurry of data, easy to implement and allow intuitively interpret the results (available scale of quantitative or qualitative assessments) without the constant involvement of experts or the decision maker.
Keywords: construction enterprise; diversification; multicriteria methods of decision making; 69.003:338.33